2018
DOI: 10.1371/journal.pone.0196803
|View full text |Cite
|
Sign up to set email alerts
|

Interference with DNA repair after ionizing radiation by a pyrrole-imidazole polyamide

Abstract: Pyrrole-imidazole (Py–Im) polyamides are synthetic non-genotoxic minor groove-binding small molecules. We hypothesized that Py–Im polyamides can modulate the cellular response to ionizing radiation. Pre-treatment of cells with a Py-Im polyamide prior to exposure to ionizing radiation resulted in a delay in resolution of phosphorylated γ-H2AX foci, increase in XRCC1 foci, and reduced cellular replication potential. RNA-sequencing of cell lines exposed to the polyamide showed induction of genes related to the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interestingly, the structural alteration caused by these minor groove-binding synthetic cyclic PIPs disrupted the binding of major groove-binding transcription factors such as the androgen and glucocorticoid receptors ( 96 ). This allosteric perturbation of the DNA helix provides a molecular basis for disruption of transcription factor−DNA interfaces by small molecules and may be applied to the chemical control of gene networks ( 97–100 ).…”
Section: Ligand-induced Structures Of the Dna Duplexmentioning
confidence: 99%
“…Interestingly, the structural alteration caused by these minor groove-binding synthetic cyclic PIPs disrupted the binding of major groove-binding transcription factors such as the androgen and glucocorticoid receptors ( 96 ). This allosteric perturbation of the DNA helix provides a molecular basis for disruption of transcription factor−DNA interfaces by small molecules and may be applied to the chemical control of gene networks ( 97–100 ).…”
Section: Ligand-induced Structures Of the Dna Duplexmentioning
confidence: 99%
“…ImP significantly blunted the increase of NF-κB after irradiation. It has been reported that the pre-treatment of glioma cells with a pyrrole-imidazole (Py-Im) polyamide prior to exposure to ionizing radiation resulted in a delay in the resolution of phosphorylated γ-H2AX foci that are indicative of the delayed repair of double-stranded breaks [ 45 ]. However, ImP, the classic downstream metabolite of l -Histidine, activated different signaling pathways to perform radioprotective functions in radiation-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Diaz‐Perez et al. (2018) 109 explored the potential of PIPs as sensitizers to genotoxic therapies. Pre‐treatment of cells with a PIP before exposure to ionizing radiation delayed the resolution of phosphorylated γ‐H2AX foci, increased XRCC1 foci, and reduced cellular replication potential.…”
Section: Designing Pips To Modulate Diverse Transcriptional Targetsmentioning
confidence: 99%